Memahami Korupsi dari Perspektif Perilaku Organisasi: Mengapa Seseorang Terjebak dalam Perilaku Korup? - Ely Susanto (Magister Administrasi Publik, 2009)
Corruption is a classical phenomenon but still interesting to be discussed. Corruption does not only contribute to negative impacts on the economic growth but also generates negative impact on the moral ground of the entire country. Many studies have investigated the determinants of corruptive behaviors. Of toe studies, two dominant approaches have been used including by previous scholars to explain corruption phenomenon; economic approach and organizational behavior approach. In this study the organizational behavior approach is used including the use of social information processing theory to theoretically explain why good people are trapped to corrupt when they are part of public organization. Detailed reason why this approach is used and how the social information processing theory explains logically the corruptive behaviors in organization ate further discussed.